Electrochemical behavior of interconnected Ti2Nb10O29 nanoparticles for high-power Li-ion battery anodes. (10th May 2017) - Pham-Cong, De; Kim, Jinwoo; Tran, Van Tan; Kim, Su Jae; Jeong, Se-Young; Choi, Jun-Hee; Cho, Chae Ryong
Graphical abstract: Highlights: Ti2 Nb10 O29 nanofibers and powders are fabricated by electrospinning and solid-state reaction process. Linearly connected single crystal nanofibers are formed. Rate capability and cycle stability of the nanofibers are enhanced compared to the powders. Diffusion behaviors of Li ion through the Ti2 Nb10 O29 single crystallite are better than other samples. Abstract: We synthesized polycrystalline Ti2 Nb10 O29 nanofibers (NFs) via a simple post-annealing process of as-electrospun polymeric NFs as an anode material for Li-ion batteries (LIBs). During the first discharge/charge process, the Ti2 Nb10 O29 NFs annealed at 900 °C exhibited insertion/extraction capacities of up to 344 and 304 mAh g −1, corresponding to 19.1 and 16.7 mol Li + per formula unit, respectively. This material exhibited excellent rate capability (93 mAh g −1 at 15 A g −1 ) and a higher average diffusion coefficient (DLi  = ∼1.5 × 10 −12  cm 2  s −1 ) than Ti2 Nb10 O29 powder (∼6.9 × 10 −13  cm 2  s −1 ). This performance can be attributed to the unique nanostructure of firmly interconnected, highly crystalline Ti2 Nb10 O29 nano-grains, which facilitates the Li + and electron transport. The kinetics obtained from current-voltage curves indicate a mixture of diffusion-limited and capacitive processes. The suggested electro-spinning/post annealing approach can effectively provide a simple route towards high-quality Ti2 Nb10 O29 NF-based anodes for high-performance LIBs.